2022
DOI: 10.1891/ijc-2021-0065
|View full text |Cite
|
Sign up to set email alerts
|

Birth-Related Perineal Tear and Its Associated Factors Among Mothers Who Delivered in Atat Hospital

Abstract: INTRODUCTIONBirth-related perineal tear or laceration(s) are related to vaginal delivery. Perineal laceration(s) can results in serious maternal morbidity and even mortality in low and middle-income countries, including Ethiopia. The prevalence and determinants of birth-related perineal tear have not been well studied in Ethiopia, particularly in the study area of this research. Therefore, the aims of this research were to determine the prevalence and determinants of birth-related perineal tear among mothers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The data collection tool was validated in Ethiopia previously. 5 , 22 Data was collected by six trained midwives with bachelor’s degrees. Questionnaires were prepared in English ( Supplemental file 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…The data collection tool was validated in Ethiopia previously. 5 , 22 Data was collected by six trained midwives with bachelor’s degrees. Questionnaires were prepared in English ( Supplemental file 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Perineal laceration(s) can result in serious maternal morbidity and even mortality in low and middle-income countries, including Ethiopia. Perineal tear is highly prevalent in Ethiopia: one study showed prevalence of perineal tear was 38.4% in Atat hospital [ 32 ].…”
Section: Introductionmentioning
confidence: 99%